Mechanical properties of ramie fiber reinforced epoxy lamina composite for socket prosthesis - Soemardi, Tresna P.; Kusumaningsih, Widjajalaksmi; Irawan, Agustinus Purna (Makara Journal of Technology, 2009)
Mechanical properties of ramie fiber reinforced epoxy lamina composite for socket prosthesis. This paper presents an investigation into the application of natural fiber composite especially ramie fiber reinforced epoxy lamina composite for socket prosthesis. The research focuses on the tensile and shear strength from ramie fiber reinforced epoxy lamina composite which will be applied as alternative material for socket prosthesis. The research based on American Society for Testing Material (ASTM) standard D 3039/D 3039M for tensile strength and ASTM D 4255/D 4255M-83 for shear strength. The ramie fiber applied is a fiber continue 100 % Ne14'S with Epoxy Resin Bakelite EPR 174 as matrix and Epoxy Hardener V-140 as hardener. The sample composite test made by hand lay up method. Multiaxial characteristic from ramie fiber reinforced epoxy composite will be compared with ISO standard for plastic/polymer for health application and refers strength of material application at Prosthetics and Orthotics. The analysis was completed with the mode of the failure and the failure criterion observation by using Scanning Electron Microscope (SEM). Based on results of the research could be concluded that ramie fiber reinforced epoxy composite could be developed further as the alternative material for socket prosthesis on Vf 40-50%. Results of the research will be discussed in more detail in this paper.